High Incidence of Contaminating Maternal Cell Overgrowth in Human Placental Mesenchymal Stem/Stromal Cell Cultures: A Systematic Review. (25th August 2014) - Heazlewood, Celena F.; Sherrell, Helen; Ryan, Jennifer; Atkinson, Kerry; Wells, Christine A.; Fisk, Nicholas M.
Abstract : Establishing the prevalence of maternal contamination has clear implications for the robustness and validity of both preclinical studies and clinical trials using placental mesenchymal stem/stromal cells (MSCs). Accordingly, we undertook a systematic review of studies investigating human placental and/or chorionic MSCs to determine the frequency and purity of maternal contamination in cultured placental chorion MSCs populations and clinical and laboratory correlates associated with maternal contamination. Abstract: Placenta is a readily accessible translationally advantageous source of mesenchymal stem/stromal cells (MSCs) currently used in cryobanking and clinical trials. MSCs cultured from human chorion have been widely assumed to be fetal in origin, despite evidence that placental MSCs may be contaminated with maternal cells, resulting in entirely maternally derived MSC cultures. To document the frequency and determinants of maternal cell contamination in chorionic MSCs, we undertook a PRISMA-compliant systematic review of publications in the PubMed, Medline, and Embase databases (January 2000 to July 2013) on placental and/or chorionic MSCs from uncomplicated pregnancies. Of 147 studies, only 26 (18%) investigated fetal and/or maternal cell origin. After excluding studies that did not satisfy minimal MSC criteria, 7 of 15 informative studies documented MSC cultures as entirely fetal, a further 7 studies reported cultured human chorionic MSC populations to be either maternal ( n = 6) or mixed ( n = 1), whereas 1 study separately cultured pure fetal and pure maternal MSC from the same placenta. Maternal cell contamination was associated with term and chorionic membrane samples and greater passage number but was still present in 30% of studies of chorionic villous MSCs. Although most studies assume fetal origin for MSCs sourced from chorion, this systematic review documents a high incidence of maternal-origin MSC populations in placental MSC cultures. Given that fetal MSCs have more primitive properties than adult MSCs, our findings have implications for clinical trials in which knowledge of donor and tissue source is pivotal. We recommend sensitive methods to quantitate the source and purity of placental MSCs.